FoxO3 regulates hepatic triglyceride metabolism via modulation of the expression of sterol regulatory-element binding protein 1c - Liu Wang (Lipids in Health and Disease, 2019)
Abstract Background Excessive intrahepatic lipid accumulation is the major characteristic of nonalcoholic fatty liver disease (NAFLD). We sought to identify the mechanisms involved in hepatic triglyceride (TG) homeostasis. Forkhead box class O (FoxO) transcription factors have been shown to play an important role in hepatic metabolism. However, little is known about the effect of FoxO3 on hepatic TG metabolism. Methods Liver biopsy samples from patients with NALFD and liver tissues from high glucose and high sucrose (HFHS) fed mice, ob/ob mice and db/db mice were collected for protein and mRNA analysis. HepG2 cells were transfected with small interfering RNA to mediate FoxO3 knockdown, or adenovirus and plasmid to mediate FoxO3 overexpression. FoxO3-cDNA was delivered by adenovirus to the liver of C57BL/6 J male mice on a chow diet or on a high-fat diet, followed by determination of hepatic lipid metabolism. Sterol regulatory element-binding protein 1c (SREBP1c) luciferase reporter gene plasmid was co-transfected into HepG2 cells with FoxO3 overexpression plasmid. Results FoxO3 expression was increased in the livers of HFHS mice, ob/ob mice, db/db mice and patients with NAFLD. Knockdown of FoxO3 reduced whereas overexpression of FoxO3 increased cellular TG concentrations in HepG2 cells. FoxO3 gain-of-function caused hepatic TG deposition in C57BL/6 J mice on a chow diet and aggravated hepatic steatosis when fed a high-fat diet. Analysis of the transcripts established the increased expression of genes related to TG synthesis, including SREBP1c, SCD1, FAS, ACC1, GPAM and DGAT2 in mouse liver. Mechanistically, overexpression of FoxO3 stimulated the expression of SREBP1c, whereas knockdown of FoxO3 inhibited the expression of SREBP1c. Luciferase reporter assays showed that SREBP1c regulated the transcriptional activity of the SREBP1c promoter. Conclusions FoxO3 promotes the transcriptional activity of the SREBP1c promoter, thus leading to increased TG synthesis and hepatic TG accumulation.